The relationship between the maqasid (higher purposes of shari'ah)approach and siyar (foreign policy of the Islamic state) - Ra'ees, Wahabuddin (IUR Press, 2010)
Classical jurists have rigorously studied siyar (the foreign policy of the Islamic state) describing the nature of the principles and norms that influenced the formulation of siyar. On the basis of these principles and norms, the jurists formulated rulings to describe the nature of the relationship of the Islamic state with others. This study examines the relationship between the principles and norms that influenced siyar and the maqasid approach (higher purposes) of shari'ah. This study first presents a conceptual analysis of siyar. Second, it discusses the approach of maqasid of shari'ah. Third, it explores selected judicial rulings taht describe the nature of siyar. Fourth, this study, building on an analysis of selected judicial rulings suggests that siyar was guided by some general principles and norms. Finally, the study examines the relationship between the principles that governed siyar and the approach of maqasid of shari'ah. The study concludes that the aim of both siyar and maqasid of shari'ah was/is to establish a moral order. The genesis of this positive relationship between the maqasid of shari'ah and the principles and norms that guided siyar is found in the unity of the source of knowledge or the principle of Divine Unity (al-Tawhid).